AB0304 Adherence To DMARD and Subcutaneous Biological Therapy among Rheumatoid Arthritis and Psoriatic Arthritis Patients at Basurto University Hospital. (15th July 2016) - Gόmez, C.; García, M.L.; Galindez, E.; Fernández, O.; Ruíz, E.; Calvo, I.; Guerrero, E.; Blanco, J.M.; Torre, I.; García, J.F.; Gorostiza, I.; Alvarez, M.M.; et al.
Abstract : Background: Combination therapy with DMARDs and Biological drugs is a common practice in the management of peripheral arthritis. The addition of Methotrexate to Biological agents provides better clinical response and decreased anti-drug antibodies production. This is well proved for patients with rheumatoid arthritis (RA), especially under therapy with anti-TNF antibodies, but not so clear for psoriatic arthritis (PsoA). Nevertheless a high percentage of patients may be non adherent, especially to DMARDs (Disease Modifying Antirheumatic Drugs), and this fact could have a negative effect on the course and management of the disease. Objectives: To assess the adherence to subcutaneous Biological drugs and DMARDs in our patients with RA and PsoA under combination therapy, and to assess the relationship between the degree of adherence and different demographic and clinical aspects. Methods: 179 clinical records of patients with PsoA and RA on Biologic treatment were reviewed. 61 patients on Biological monotherapy were excluded from the analysis. Demographic, clinical characteristics and comorbidities were collected. The level of adherence to DMARDS was obtained from the PRESBIDE monitoring system that estimates external pharmacy drug picking up for the last 8 months, and data of adherence to Biologicals from the Hospital Pharmacy registry (FARHOS). SPSSv22 software was used for statistical analysis. Results: 109 patients included, 76% women, mean aged 57 years (range 19–86). 70% had RA and 30% PsoA. Disease evolution was longer than 10 years in 63% of the patients. 32% presented more than two comorbidities. Concerning DMARDs, 76% of patients received Methotrexate, 15.6%Leflunomide and 8.4% others. Average adherence to DMARDs was 65.5%, being good (>80%) in 49.5%, fair (60–80%) in 22% and low (<60%) in 28.4%. In 13 patients (11.92%) DMARD collection at the pharmacy was 0. Evaluated Biological drugs were mainly Adalimumab (30%) and Etanercept (39.5%). Adherence to Biologicals was excellent, average 91.8% (SD 9.78), significantly higher than the adherence to DMARDs (average 65.53, SD 32.79). (p<0.001, WR test). Disease activity estimated by DAS 28 was<2.6 in 57% of patients, 2.6–3.2 in 19, 6% and >3.2 in 23.4%. There was no correlation between lack of adherence and resulting DAS 28. 47.7% of patients had received more than one DMARD previously, fact not being related to the current adherence. No relationship between the number of previous Biological drugs and adherence to DMARD was found. Conclusions: Adherence to subcutaneous Biologic agents was good and statistically superior to Methotrexate. A high proportion of our patients (1/3) is non adherent to DMARDs, so that more than 10% are under unexpected monotherapy with Biological drugs because of noncompliance or withdrawal of the treatment. The reasons for this may be various, and the impact on the disease activity must be evaluated, as far as both negative and neutral effect had been described in the literature. The implementation of tools to monitor adherence and identification of non-compliant patients is useful in the search of solutions and clinical decision making. Disclosure of Interest: None declared